Recent technology development in radiotherapy for intracranial meningiomas - Ungar, Rebecca; Kilian-Meneghin, Joshua; Eckroate, Brett; Motwani, Sabin; Yue, Ning; Nie, Ke; Xiong, Zhenyu; Zhang, Yin (Frontiers in Neurology, 2025)
Meningiomas are the most common central nervous system (CNS) tumors in the United States. Radiotherapy plays an important role in the management of meningiomas and has been established as an effective means of local tumor control. The recent technology development in artificial intelligence, understanding of meningioma biology and molecular imaging, will likely impact the clinical management of meningiomas, including treatment efficacy, efficiency and safety. This review summarizes recent technological advances that may influence radiotherapy management for meningiomas, including external beam radiation therapy, proton therapy and brachytherapy.